Sifat Fisis Mekanis Papan Partikel dari Serat Sisal atau Serat Abaka setelah Perlakuan Uap Physical and Mechanical Properties of Particleboard Made from Steamed Treated Sisal or Abaca Fibers - Firda A Syamani; Kurnia W Prasetyo; Ismail Budiman; Subyakto Subyakto; Bambang Subiyanto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2008)
Composites made from natural fibers have several weakness, particularly on thickness swelling, due to fiber dimensional changes during swelling of fiber cell wall or changing of lumen dimension by moisture uptaken. Steam treatment on fiber had been expected could reduced fiber water absorbancy by plasticized matrix of fiber cell walls. Fiber of Sisal and Abaca was chopped into 0.5 ~ 2.0 cm of length. Steam treament was conducted in autoclave for 30 minutes on 1.15 atm of pressure and 121ºC of temperature. Chopped fiber was dried in 60ºC oven to obtain 4% of moisture content. Dried fiber was mixed with 10% urea formaldehyde (UF) resin or 8% and 10% melamine urea formaldehyde (MF) resin (based on weight of fiber oven-dried). Glued fiber was formed into 25cm x 25cm x 0.8cm mat, then hot pressed at 20 kgf/cm2 pressure for 10 minutes. Target density was 0.7 g/cm3. Composites conditioning was conducted at room temperature for moisture equilibrium to the enviroment. Physical dan mechanical characteristics testing was carried out based on JIS A 5908 for particle board. Steam treatment could improved physical and mechanical properties of particleboard made from sisal fiber using 8% MF.